The Influence Of Work load, Self-Efficacy And Work Ethic On Burnout And Work-Life Balance And Performance Of Hospital Nurses In Surabaya (International Journal of Scientific Research and Management (IJSRM), 2025)
Hospital management highlights the importance of studying the performance of medical personnel, including doctors, nurses, and other healthcare workers, as well as non-medical staff such as administrative personnel and operational human resource employees. This research aims to analyze the effects of workload, self-efficacy, and work ethic on burnout and work-life balance, and how these factors impact nurses’ performance. The study was conducted at an hospital located in Surabaya. It employed a quantitative approach by distributing questionnaires using a saturated sampling technique to 135 respondents, consisting of both medical and non-medical employees working at the hospital. The data analysis technique used to test the hypotheses was structural equation modeling (SEM) with the AMOS program.The results revealed that workload and self-efficacy each have a significant negative impact on burnout. Workload significantly negatively affects work-life balance, while self-efficacy significantly positively affects work-life balance. Both self-efficacy and work-life balance significantly positively impact nurses’ performance, whereas workload significantly negatively impacts nurses’ performance. Work ethic negatively but insignificantly influences burnout and does not significantly positively affect work-life balance or nurses’ performance. Additionally, burnout negatively but insignificantly impacts work-life balance.